2013
DOI: 10.1167/iovs.13-11756
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin-Induced Dilation of Isolated Porcine Retinal Arterioles via Production of Nitric Oxide From Endothelial Cells

Abstract: Adiponectin elicits mainly endothelium-dependent dilation of the retinal arterioles. Endothelium-dependent vasodilation likely induced by adiponectin results from NO via activation of guanylyl cyclase that is partially dependent on AMPK activity. Understanding the effect of adiponectin on the retinal vasculature may help improve potential therapies for retinal vascular disorders, especially diabetic retinopathy in patients with type 2 diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 53 publications
2
27
0
Order By: Relevance
“…The magnitude of adiponectin‐induced vasodilation was consistent with previous studies of porcine retinal arterioles (Omae et al . ), but did not achieve a magnitude of dilation comparable to either adenosine or ACh (Figure A,B).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The magnitude of adiponectin‐induced vasodilation was consistent with previous studies of porcine retinal arterioles (Omae et al . ), but did not achieve a magnitude of dilation comparable to either adenosine or ACh (Figure A,B).…”
Section: Resultsmentioning
confidence: 90%
“…Adiponectin, itself, has previously been shown to exert vasodilator actions via a mechanism that is at least, in part, dependent on the endothelium . Furthermore, as the dilation is inhibited by NOS inhibitors, the vasomotor response requires NO . This series of signaling events also appears to involve activation of AMPK .…”
Section: Introductionmentioning
confidence: 99%
“…Other studies showed that adiponectin suppressed the TNF-a-stimulated expression of E-selectin, VCAM-1 and ICAM-1 in human endothelial cells [38]. Adiponectin elicits mainly endothelium-dependent dilation of the retinal arterioles [39]. Endothelium-dependent vasodilation likely induced by adiponectin results from NO via activation of guanylyl cyclase that is partially dependent on AMPK activity, thus low serum levels of adiponectin may explain our findings of a lower RHI index in subjects with diabetic foot.…”
Section: Discussionmentioning
confidence: 99%
“…After ADP binds to its receptor, the biological effects of ADP on insulin sensitivity seem to be mediated by its ability to activate AMPK, MAPK, and peroxisome proliferator-activated receptors-α signaling pathways, resulting in an increase of fatty acid oxidation and glucose uptake in muscle tissue, as well as an inhibition of gluconeogenesis in the liver [62]. In addition, ADP can also promote the production of endothelial nitric oxide to exert anti-atherosclerotic effects by improving the vascular dysfunction and inhibiting vascular inflammation [64,65]. With the deepening of research, it has been found that osteoblasts can express ADP and its receptors, and it can be concluded that ADP may be a key factor in metabolic bone disease [66].…”
Section: Oc and Exercisementioning
confidence: 99%